Japan at war : - Cook, Haruko Taya (Distributed by Norton, 1992)
In a sweeping panorama, Haruko Taya Cook and Theodore F. Cook take us from the Japanese attacks on China in the 1930s to the Japanese home front during the inhuman raids on Tokyo, Hiroshima, and Nagasaki, offering the first glimpses of how the twentieth century's most deadly conflict affected the lives of the Japanese population.